2020
DOI: 10.37992/2020.1101.053
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability studies for yield and its component traits in newly developed sunflower (Helianthus annuusL.) hybrids

Abstract: The present study was conducted in order to estimate the genetic variability and variability parameters among the parental lines and crosses for 18 characters in sunflower. The investigation was carried out at Regional Agricultural Research Station, Nandyal during rabi, 2018-19, in a Randomized block design with two replications. ANOVA studies reported highly significant differences for all the traits. High GCV and PCV recorded for oil yield, leaf area index, seed yield, autogamy per cent, number of seeds per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Sonu Kumar et al, [26] recorded "high heritability coupled with high genetic advance for days to 50% flowering, days to maturity, plant height etc". "High heritability and genetic advance noted for leaf area index, plant height, specific leaf area, the number of leaves per plant, oil yield, seed set per cent, seed yield, 100 seed weight, the number of seeds per head, head diameter and autogamy per cent" by Varalakshmi et al, [16]. "High values of phenotypic and genotypic coefficient of variability, and high heritability with high genetic advance were observed for seed yield/plant, oil yield/plant.…”
Section: Variability and Heritabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Sonu Kumar et al, [26] recorded "high heritability coupled with high genetic advance for days to 50% flowering, days to maturity, plant height etc". "High heritability and genetic advance noted for leaf area index, plant height, specific leaf area, the number of leaves per plant, oil yield, seed set per cent, seed yield, 100 seed weight, the number of seeds per head, head diameter and autogamy per cent" by Varalakshmi et al, [16]. "High values of phenotypic and genotypic coefficient of variability, and high heritability with high genetic advance were observed for seed yield/plant, oil yield/plant.…”
Section: Variability and Heritabilitymentioning
confidence: 97%
“…[6], Sutur et al [16] and Reena et al [15] reported the highest variation for plant height, Supriya et al [17] and Latha et al [18] for seed yield. It can be observed from the results that all the characters showed closer values of PCV and GCV (Table 3).…”
Section: Variability and Heritabilitymentioning
confidence: 99%